Sistema de informação geográfica para vitivinicultura no município de Nova Pádua/RS - Souza, Mariângela Gil de (Universidade do Vale do Rio dos Sinos, 2016)
The study was conducted at Boscato Industry Winery Ltda., located on the upper slopes of the northeast region of Rio Grande do Sul, on top of the Vale do Rio das Antas, Serra Gaucha, municipality of Nova Padua, belonging to Indication of Origin Montes Altos. The software used for this work and construction of a Geographic Information System (GIS) for Viticulture was ArcGis, which prepares and handles information for use and management of thematic bases, composed of several integrated tools, easy to use, which help to obtain the final result. The GIS is part of one of the many technologies used in precision farming that has the general objective, the management of variability of soil and crops in space and time. Precision agriculture involves soil variability aspects, climate and diversity of cultures. The work aimed to unite the georeferencing with viniculture, allowing the rural producer has an accurate map of the vineyard, assisting in the planning and management of the property and the wine, making this union in a winegrowing precision, getting a crop selective with good productivity and excellent results of harvest. The flexibility of geographic information systems (GIS) allows data collected field (points by GPS and production), linked to pedological, climatic data, land use, create a practically complete characterization of Nova Padua region.
Keywords: SIG; Georrefenciamento; Vitiviniculta; Georeferencing; Viticulture